PENGARUH TERAPI MUSIK KLASIK (MOZART) TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS SEI LANGKAI - Istiqomah Rilladya; Trisya Yona Febrina; Rurry Nindya Taluphyta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Hypertension is a non-communicable disease which is one of the main causes of premature death in the world. From the 2015 WHO data, it shows 1.13 billion people in the world suffer from hypertension, meaning that 1 in 3 people in the world are diagnosed with hypertension, hypertension is more common in the elderly and the elderly than in younger age groups. In Indonesia alone, the number of people with hypertension at the age of 65-74 years is 63.2% and >75 years is 69.5% with the total percentage of deaths in the elderly group in June 2020, amounting to 43.60%. In Batam City, hypertension occupies the 4th position with the highest number of cases with 139,160 cases. This research is a quasi-experimental research with a quasi-experimental design with a pre and post test design. The sampling technique used was non-probability sampling, namely purposive sampling with a sample of 16 elderly people in the treatment group and 16 elderly people in the control group. Data collection techniques were carried out through direct measurements using a digital sphygmomanometer, headset, mp3 player, soup and measurement observation sheets. Statistical results using the Wilcoxon signed rank test were obtained. There was a significant difference between the average blood pressure values (systolic and diastolic) before and after therapy. classical music (Mozart) in the treatment group with p<0.05 (systolic p-value 0.000 and diastolic p-value 0.001). While in the control group there was no significant difference between the average blood pressure values (systolic and diastolic) before and after without classical music therapy (Mozart) with p>0.05 (systolic p-value 0.130 and diastolic p-value 0.102).